ANTHELMINTIC ACTIVITY OF CARUM CAPTICUM SEEDS AGAINST GASTRO- INTESTINAL NEMATODES OF SHEEP - M. Lateef; Z. Iqbal; U. Rauf; A. Jabbar (Journal of Animal and Plant Sciences, 2006)
This paper describes in-vivo anthelmintic activity of Carum copticum in comparison with levamisole. For invivo studies, the seeds of Carum copticum was administered as crude poweder (CP), Crude equeous extract (CAE) and crude methanol extract (CME) at graded doses (1,2 and 3 g kg-1body weight (b.w.) to sheep naturally infected with mixed species of gastrointestinal nematodes. Maximum reduction (79.1%) in eggs per gram (EPG) of faeces was recorded on day 14 post treatment in sheep treated with Carum copticum CP at 3g kg-1b.w. It was found that although, carum copticum seeds possesses anthelmintic activity against nematodes, it is not comparable with levamisole (99.2% reduction in EPG) at any of the doses tried in this study. However, increase in EPG reduction was noted with an increase in the dose of Carum copticum administered as CP, CAE and CME. The graded dose response suggested further studies on a larger number of animals on higher doses than those used in the current study.
Keywords: Anthelmintic; Carum copticum; levamisole crude aqueous extract; crude methanol extract